Use of social media in education among medical students in Saudi Arabia - Anas Khaleel Alsuraihi; Ahmed Saeed Almaqati; Sultan Adnan Abughanim; Nisreen Abdulrahman Jastaniah (Korean Journal of Medical Education, 2016)
Purpose Social media (SM), a virtual place where people can share, exchange, and communicate their ideas and knowledge, has become the new trend in communication and learning. This study aims to explore Saudi Arabian medical students’ usage of SM and to discover the most common resources used in medical education. Furthermore, it aims to illustrate students’ belief about the influence of SM on their learning. Methods This cross-sectional study administered validated questionnaires to medical students from different universities in Saudi Arabia, via emails, Twitter, Facebook, and short message service. A non-probability sampling technique was utilized and a sample size of 381 students was arrived at, using 95% confidence interval and 5% margin of error, since the total number of medical students in Saudi Arabia is approximately 36,000. The total respondents were 657 students from 23 different Saudi Arabian medical schools (females: 60.5%, n=397; males: 39.5%, n=260). Results The questionnaires of 21% of the students (n=139) were excluded from the analysis since they were incomplete. The most common website used by both genders was YouTube (42.3%, n=185); however, males preferred using Twitter and Wikis (p=0.001). With regard to utilizing SM for learning, 95.8% (n=419) of the students believed that it is beneficial. Females stated that SM helps them link basic and clinical science (p=0.003). Conclusion Medical schools need to improve the utilization of SM by their faculty and students by developing activities and encouraging the usage of SM in education.